QUANTIFYING THE RISK OF ABNORMAL NEUROPHYSIOLOGY AS A RESULT OF SUB-CONCUSSIVE BLOWS IN HIGH SCHOOL FOOTBALL ATHLETES. Issue 7 (11th March 2014) - Leverenz, L; Breedlove, K; Breedlove, E; Robinson, M; Poole, V; King, JR; Rosenberger, P; Rasmussen, M; Talavage, T; Nauman, E
Abstract : Background: Recent work suggests that repetitive sub-concussive head impacts may contribute to long-term neurodegeneration; however, the risk thresholds for sub-concussive injury are unknown. Objective: To evaluate the risk of developing abnormal neurophysiology due to repetitive impacts to the head. Hypothesis: the number of head impacts is predictive of neurological impairment. Design: ImPACT, fMRI, and head impact telemetry (HIT) was employed in baseline tests, pre-season and in-season. The number and magnitude of head impacts were collected for practices and games. Setting: American high school football. Participants: 13 high school American football players age 14–18. Those diagnosed with a concussion were excluded. Risk factor assessment: The number of head impacts during the season. Main outcome measurements: Pre-season and in-season ImPACT, MRI, and fMRI. Results: The players experienced an average of 17.7 to 45.5 hits/week with a mean and standard deviation of 71.7±39.3. The corresponding cumulative number of hits for the season ranged from 86 to 1996 with a mean and standard deviation of 582.8±444.3. Twenty-two in-season ImPACT tests were administered during the season. Twelve (54.5%) showed a minimum of one composite score flagged, the fMRI analysis showed 16 (72.7%) in-season assessments flagged, and seven subjects were flagged by both the ImPACT and fMRI. Groups were divided based on number of head impacts; those above & below 500 cumulative hits/season and above and below 65 hits/week. Above 500 cumulative hits/season and 65 hits/week, all examinations were flagged. Conclusions: A number of asymptomatic athletes exhibited neurophysiological changes. The number of head impacts is a risk factor for the development of neurophysiological changes. The medical staff should monitor players who are taking large numbers of hits, consider using neurocognitive testing on an annual basis, and promote proper technique and skill development for the players.